The Place of Historical Omens in the System of Apodoses - Starr, Ivan
ersch. 1987; Appendix A: Bearbeitung von K. 2130 (4R 34, King, CCEBK II 129-137); BM 67404; Appendix В: BM 61665, Kopie, Bearbeitung.